Polymorphism of keratin-associated protein (KAP) 7 gene and its association with wool traits in Rambouillet sheep - MAHAJAN, VIKAS; DAS, A K; TAGGAR, R K; KUMAR, DHIRENDRA; SHARMA, RAJAN (The Indian Journal of Animal Sciences, 2018)
In the present study, association of polymorphic variants of KAP 7 gene with wool traits in Rambouillet sheep was investigated by using SSCP-PCR. Genomic DNA was isolated from blood samples of 100 Rambouillet sheep. A 388 bp segment was amplified by PCR using ovine specific primers for KAP 7 gene. The results identified 3 genotypes, viz. AA, AB and BB with genotype frequencies of 0.340 (34), 0.270 (27) and 0.390 (39) respectively and allele frequencies of 0.475 for allele A and 0.525 for allele B. The χ²-test showed that the genotype distribution was not in agreement with Hardy-Weinberg equilibrium (HWE). KAP 7 gene has significantly higher clean wool yield and greasy fleece weight in males whereas females have significantly superior fibre diameter, higher staple length and wool count. BB genotype has significantly higher staple length followed by AA and AB genotype. BB genotype has significantly higher greasy fleece weight production followed by AB and least by AA genotype. From the study, it may be concluded that KAP 7 gene might be a potential molecular marker for genetic selection for higher staple length and greasy fleece weight in Rambouillet sheep.